A Comparison of Management Processes in Educational Hospitals Located in Isfahan, Iran - Seyed Majid Shirzadi; Somayeh Safdari; Zahra Hashemidehaghi; Ali Ayoubian; Sosan Bahrami (CES Working Papers, 2015)
Hospitals are service organizations and act as the main health and treatment institutes in the society. To achieve organizational goals, hospitals need to implement a proper management system. The present study tries to compare management processes in educational hospitals located in Isfahan, Iran between 2009 and 2012. Study population of this descriptive-survey research was comprised of all nursing managers in the educational –treatment clinics affiliated with Isfahan Medical Science University. Sample (n = 165) was selected through census sampling. A standard questionnaire based on Stoner's model (1995) was used for data gathering. Validity of the questionnaire was tested using face and content validity and reliability of the questionnaire was checked by Cronbach's alpha (a = 0.85). For data analyzing, descriptive statistics and inferential statistics such as independent t-test ANOVA, MUANOVA and LSD were used in SPSS (ver.18). In 2009, the t-value for all the managerial processes were less than error level (0.05) in 2012 and; therefore, the four managerial processes were lower than the mean level. Comparison of managerial processes in the educational hospitals located in Isfahan based on demographical variables showed that obtained F for 2012 was significant (P=0.05). Furthermore, means of programming, leadership, and control processes of the participant hospitals, based on education degree, were different. Proper management is the key to meet the organizational goals and surveying managerial processes can be a large step to improve efficiency and effectiveness of the organization.
Keywords: I1; I2; 330; programming; organizing; leadership; supervision and control; educational hospital